GOAT ECTOPARASITOSIS - Pulotov F.S. PhD; Boltaev D.M (Western European Studies, 2024)
The article presents information on the spread of ectoparasites and ectoparasitises among goats
Keywords: Bovicolosis; lice; ticks; linognathosis